'The purest citizens' and 'IVF children'. Reproductive citizenship in contemporary Poland. (December 2016) - Korolczuk, Elżbieta
Abstract: This article examines the public debate on reproductive technologies in contemporary Poland, focusing on the rhetorical strategies used by the main opponents of IVF: conservative politicians representing the leading parties in the Polish parliament and the representatives of the Catholic Church. The analysis highlights the exclusionary logic inscribed in the construction of the main categories of political subjects in this debate, revealing important limitations of reproductive citizenship in the Polish context. The study draws on a variety of texts published in print and electronic media between 2007 and 2015, including articles on infertility and reproductive technologies published in the main Polish daily and weekly print publications, online resources (web pages, forums and Facebook pages), documents issued by the representatives of the Church, politicians and experts, e.g. open letters, commentaries, information for the media and interviews.